2020
DOI: 10.1177/0954406220952504
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different welding methods on mechanical properties and formability behaviors of tailor welded blanks (TWB) made from AA6061 alloys

Abstract: A tailor welded blank (TWB) includes two or more blanks joined together in order to make a single blank. Different welding methods are used to join blanks with different characteristics and form TWBs. In this study, a comparison is made among the effects of three different welding methods namely CO2 laser welding, friction stir welding (FSW), and friction stir vibration welding (FSVW) on mechanical and formability properties of developed TWBs. AA6061 alloy sheets with different thicknesses (1.2 and 0.8 mm) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…This reduction in grain size can be ascribed to the lower strain rate and processing temperature at a higher travelling speed. 39 These finer grains with increased volume fraction of grain boundaries in the microstructure blocked the movement of dislocations and enhanced strength according to the Hall–Petch equation ( σ = σ 0 + kd −0.5 , where K and σ 0 are constants) as reported by Behrouz et al 40…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…This reduction in grain size can be ascribed to the lower strain rate and processing temperature at a higher travelling speed. 39 These finer grains with increased volume fraction of grain boundaries in the microstructure blocked the movement of dislocations and enhanced strength according to the Hall–Petch equation ( σ = σ 0 + kd −0.5 , where K and σ 0 are constants) as reported by Behrouz et al 40…”
Section: Resultsmentioning
confidence: 70%
“…This reduction in grain size can be ascribed to the lower strain rate and processing temperature at a higher travelling speed. 39 These finer grains with increased volume fraction of grain boundaries in the microstructure blocked the movement of dislocations and enhanced strength according to the Hall-Petch equation (σ = σ 0 + kd −0.5 , where K and σ 0 are constants) as reported by Behrouz et al 40 The specimen FSPed at an increased rotational rate of 1200 r/min and 30 mm/min traverse speed exhibited an increased grain size of 4.16 μm (Figure 4(a)) with 81.35% finer grains (Figure 4(b)) with 15.79% LAGBs and 72.42% HAGBs (Figure 4(c)). The reduction of ultrafine grains and the presence of coarser grains (8.83%) as shown in Figure 4(b) confirmed the occurrence of grain growth due to heat input.…”
Section: Microstructural Observations Using Ebsd and Afmmentioning
confidence: 71%
“…In a wide range of industrial applications, including those in the shipping, automotive, aerospace, marine, and robotics industries, FSW triumphs over all other traditional welding techniques [4][5][6]. FSW is one of the solid-state welding techniques that can produce joints between dissimilar alloys more efficiently than fusion welding techniques [7,8]. This method affects the development of a joint while the material is still solid by causing deformation and frictional heat at the welding zone [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The literature on Etesami et al [10] noticed that aging heat treatment can be used to lower residual stress and also reduce the deformation of TC4 parts during the laser-based powder-bed fusion (L-PBF) additive manufacturing process, but could not significantly alter the strength and ductility of welded joints. Bagheri et al [11] studied the use of different welding methods to connect billets with different characteristics and form a tailor-welded blank (TWB) and found that the forming limit diagram (FLD) for TWBs made by friction stir welding (FSW) is higher than FLD for TWBs made by CO2 laser welding, and FLD 0 for TWBs made by friction stir vibration welding (FSVW) increases as vibration frequency increases. Nie et al [12] reviewed the research progress of cutting imaging technology, analyzed the important physical quantities of the chip formation process obtained from cutting imaging, revealed the advantages and importance of cutting imaging, and looked forward to its future development direction.…”
Section: Introductionmentioning
confidence: 99%